Interlocking practices and their influence in the home - Breadsell, J.; Eon, C.; Morrison, Greg; Kashima, Y. (2019)
© The Author(s) 2019. When people move into sustainable houses, they bring practices with them that have temporally evolved along with their daily lives. A common misconception is that change to individuals’ resource use can be persuaded without consideration of previous practices. However, it has been observed that energy efficient or smart buildings do not always perform as expected due to a lack of occupant skills, time or motivations. The successful adoption of technology is dependent on the understanding of these underlying practices, which should be considered at the building planning stage. The recently developed concept of the Home System of Practice was employed in this research to study home dwellers through living laboratory mixed methods, allowing for an in-depth examination of their daily lives, routines, habits and practices. The personal hygiene, thermal comfort, clothes drying, garden watering and waste practices of 14 households were examined. Results identified Home System of Practices with different degrees of interlocking and highlighted how various combinations of meaning, skill and technology elements of a practice as well as contextual influences can affect resource use. These insights can be used by urban planners to facilitate a co-creation process with end-users and develop innovative solutions to enable resource reduction while ensuring that resident needs and comfort are maintained.